Implementasi Kebijakan Pembangunan SDGs Desa Era Covid 19 di Kabupaten Simeulue Aceh - Nellis Mardhiah Nellis; Zuhrizal Fadhly; Siti Jahriah Situmpol (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2023)
Implementation of public policies in the development of village SDGs in the aspect of achieving goal-II which prioritizes food security for the community in the COVID-19 era in a sustainable manner. This area is also an agricultural base where there are always conflicts over land grabs between farmer groups and planting plans according to local cultural demographics. Ironically, the government has provided a village development budget every year in the management of agricultural aspects, but this cannot be understood on a continuous basis by SKPK and village officials in achieving the objectives of the strategic plan. Qualitative research methods that focus on social solutions in real life, both individual practical problems or community groups and the impact can be felt directly by the community. Technical data collection through primary data and secondary data. Primary data, FGD. Interviews in this study are semi-structured (Semi-Structured Interview) and are carried out individually and in groups. The results of the study show that the implementation of village SDGs development policies in the aspect of achieving goals-II in the covid19 era is not optimal, there are still challenges in communication patterns that are not in the direction of the government and village governments, resources are not competent and the budget is still limited. However, the Goal-II village SDGs policy has an opportunity in community development that is normally understood and realized by the local government of the presence of customary institutions in accordance with Qanun Number 8 of 2010 in Aceh. This position will be strengthened by village government organizations in the future so that food security development can be achieved according to community expectations